ANTIBIOTIC RESISTANCE, MECA GENE DETECTION, AND BIOFILM FORMATION ABILITY AMONG COAGULASE-NEGATIVE STAPHYLOCOCCI IN CANCER PATIENTS - TK, DILSHA; SAMUEL, SAJANI; RUDRAPATHY, PARTHIBAN; MURUGESAN, SARAVANAN; KE, SARATH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to identify coagulase-negative staphylococci (CoNS) from various clinical samples and to determine the antibiotic resistance of the isolates by means of automation (VITEK-2), as well as to detect biofilm formation using Congo red agar method and to detect mecA gene by automated identification method (VITEK-2). Methods: All the clinical samples (blood, urine, sputum, BAL, throat swab, wound swab, aspirated fluid, pleural fluid, and pus) received in the microbiology laboratory were processed by aseptic techniques. Clinical samples were inoculated on appropriate media (blood agar, MacConkey agar, and chocolate agar [HIMEDIA]). After inoculation, the culture plates were incubated at 37°C aerobically for 18–24 h for growth. Positive cultures were picked up and further bacterial species identification was done using automated techniques (MALDI- TOF). Results: Among 28 isolates, the most recurrent strains of CoNS are Staphylococcus epidermidis, Staphylococcus hominis, Staphylococcus lugdunensis, and Staphylococcus haemolyticus. The assessment of antibacterial drugs sensitivity shows that all the isolates were more sensitive to daptomycin (S. epidermidis 100%, S. hominis 100%, S. lugdunensis 100%, and S. haemolyticus 42.85%) followed by linezolid (S. epidermidis [69.23%], S. hominis [100%], S. lugdunensis [100%], and S. haemolyticus [57.14%]) and vancomycin (S. epidermidis [100%], S. hominis [40%], S. lugdunensis [100%], S. haemolyticus [42.85%]). The analysis revealed the presence of the mecA gene (67.85%) and biofilm production (85.71%), respectively. Conclusion: Our data indicate that the hospital environment can be colonized by biofilm forming CoNS and transmission of these strains can cause an increased risk of serious nosocomial infections.